Pengaruh Penggunaan Media Boneka Jari terhadap Kemampuan Berbicara Anak di Paud Arifah Kec. Medan Perjuangan Tahun Ajaran 2021-2022 - Ariska Hardiati; Darajat Rangkuti (Medan Resource Center, 2022)
The purpose of this research is to explain whether there is a positive and significant effect of using finger puppet media on the speaking ability of children in Paud Arifah Kec. Battlefield? The type used in this research is the pre-experimental method and the research design used in this study is a one group pretest and posttest design. The population in this study were all children in PAUD Arifah Kec. Medan Perjuangan T.A 2021-2022 which consists of a class of 15 children with a research sample of 15 children consisting of 7 boys and 8 girls. Data collection techniques used are observation and documentation. Based on the results of the t test, the value of tcount> ttable is 16.57 > 2.144 at the level of = 0.05 which states that Ho is rejected and Ha is accepted. So it can be stated that H0 is rejected and Ha is accepted, which means that there is an effect of using finger puppet media on children's speaking ability at PAUD Arifah, Medan Perjuangan District T.A 2021-2022. Thus, the hypothesis proposed is that there is a significant effect using finger puppet media on the speaking ability of children in Paud Arifah Kec. Field of Struggle T.A 2021-2022.